Author’s agency in a research article: From the grammar of language to the grammar of communication - S. A. Sheypak (Образование и наука)
Introduction. Writing for publication has been developed for two last decades as an independent field of research to help authors publish their research articles. Starting from the assessment that preparing the publication in a journal is an academic activity that requires learning to construct the author’s positioning in the manuscript, this paper points out the shortage of professionals to assume institutional organisation of training courses in Russia.Aim. This paper aims to suggest a framework for informal practices based on autonomy and the collective organisation of authors to construct an authorial position in the manuscript or author’s agency toward a target journal.Methodology and research methods. Various approaches applied in this paper are based on activity theory: situated learning, Change Laboratory, and expansive learning.A review of Russian and foreign research in writing for publication shows that only one of the three types of authorial agency, that is, transformative agency, might help the author to prepare a manuscript for publication in a target journal. The framework needed for emerging author’s transformative agency re-conceptualises the model of the Change Laboratory for situated learning that aims at the author’s socialisation in the discursive practices of a target journal. Situated learning for writing for publication is based on the principles of the Change Laboratory: collectivity; double stimulation; overcoming the contradiction by ascending from the abstract to the concrete.Results. A framework for three cycles of expansive learning aimed at the emergence of the author’s agency toward a target journal has been developed. The first cycle allows selecting a journal and revealing its implicit rules for manuscript production. The second cycle is focused on step-by-step manuscript revisions. Finally, a change of journal and/or author whose manuscript is discussed involves the third cycle of expansive learning.Scientific novelty. The paper considers manuscript production for publishing in a journal as an academic activity requiring deliberate training in native and foreign languages. The framework for three cycles of expansive learning in writing for publication conceptualises the publication as the author’s participation in social practices involving the journal as a discursive community.Practical significance. The framework suggested in this paper for emerging transformative agency in writing for publication might imply an alternative to the institutional training courses. Three cycles of expansive learning aim to develop the author’s publication competence and improve the quality of research articles.